2020
DOI: 10.1111/nph.16745
|View full text |Cite
|
Sign up to set email alerts
|

The root‐knot nematode effector MiPDI1 targets a stress‐associated protein (SAP) to establish disease in Solanaceae and Arabidopsis

Abstract: Large amounts of effectors are secreted by the oesophageal glands of plant-parasitic nematodes, but their molecular mode of action remains largely unknown. We characterized a Meloidogyne incognita protein disulphide isomerase (PDI)-like effector protein (MiPDI1) that facilitates nematode parasitism. In situ hybridization showed that MiPDI1 was expressed specifically in the subventral glands of M. incognita. It was significantly upregulated during parasitic stages. Immunolocalization demonstrated MiPDI1 secreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 66 publications
6
33
0
Order By: Relevance
“…Microarray analysis on Arabidopsis gapc mutants showed that several genes encoding for enzymes regulating reactive oxygen species (ROS) homeostasis, such as peroxidases, catalases, or superoxide dismutases, had altered expression (Rius et al, 2008), and here, using a RT-qPCR approach, we demonstrated a differential expression of defense-and stress-associated genes in abp39 and abx27 mutants, both mutant lines showing strong constitutive expression of AtPR1a and AtPDF1.2a genes. While several RKN effectors were shown to be responsible for host defense suppression (Quentin et al, 2013;Vieira and Gleason, 2019), very few have had their host target identified, i.e., MiMIF2 (Zhao et al, 2019), MiPDI1 (Zhao et al, 2020), Mg16820 (Naalden et al, 2018), MgMO237 (Chen et al, 2018), and MjTTL5 (Lin et al, 2016). This work adds MiEFF1 to the list of RKN effectors modulating host immunity and confirms that defense-and stress-related proteins are key targets of effectors, particularly those of nematodes, during disease establishment.…”
Section: Discussionsupporting
confidence: 56%
See 4 more Smart Citations
“…Microarray analysis on Arabidopsis gapc mutants showed that several genes encoding for enzymes regulating reactive oxygen species (ROS) homeostasis, such as peroxidases, catalases, or superoxide dismutases, had altered expression (Rius et al, 2008), and here, using a RT-qPCR approach, we demonstrated a differential expression of defense-and stress-associated genes in abp39 and abx27 mutants, both mutant lines showing strong constitutive expression of AtPR1a and AtPDF1.2a genes. While several RKN effectors were shown to be responsible for host defense suppression (Quentin et al, 2013;Vieira and Gleason, 2019), very few have had their host target identified, i.e., MiMIF2 (Zhao et al, 2019), MiPDI1 (Zhao et al, 2020), Mg16820 (Naalden et al, 2018), MgMO237 (Chen et al, 2018), and MjTTL5 (Lin et al, 2016). This work adds MiEFF1 to the list of RKN effectors modulating host immunity and confirms that defense-and stress-related proteins are key targets of effectors, particularly those of nematodes, during disease establishment.…”
Section: Discussionsupporting
confidence: 56%
“…The M. incognita MiEFF1 (Minc17998; GenBank MW345915) and MiEFF18 (Minc18636; GenBank KX907770) coding sequences (CDS) lacking the signal peptide, the A. thaliana AtUSP (At3g53990), AtGAPC1 (At3g04120), AtGAPC2 (At1g13440), and AtSmD1b (At4g02840), the AtUSP and AtGAPC2 promoters, the SV40 T antigen and the murin P53 sequences were amplified by PCR with specific primers (Supplementary Table 1) and inserted into the pDON207 donor vector. The entry clones were recombined with pK7WGF2 (p35S:eGFP-GW), pK7WGR2 (p35S:RFP-GW), pKGWFS7 (GWpromoter:eGFP-GUS), BiFC vectors (pAM-35SS:GW-YFPc, pAM-35SS:GW-YFPn, pAM-35SS:YFPc-GW, and pAM-35SS:YFPn-GW) or Y2H vectors, pGBK-GW, pB27-GW, or pP6-GW (Karimi et al, 2002;Caillaud et al, 2009;Zhao et al, 2020), with Gateway technology (Invitrogen). All constructs were sequenced (GATC Biotech) and used to transform Agrobacterium tumefaciens strain GV3101 or Saccharomyces cerevisiae strains AH109, L40ΔGal4, or Y187.…”
Section: Plasmid Constructsmentioning
confidence: 99%
See 3 more Smart Citations